The effectiveness of a health literacy enhancement program on knowledge, self-management behaviors, and clinical outcomes in people with chronic kidney disease: A quasi-experimental study in Thailand - Piyaporn Inthaphalan; Jiraporn Lininger; Sangthong Terathongkum (Belitung Raya Foundation, 2024)
Background: Chronic kidney disease (CKD) is a leading cause of death, with a rising incidence worldwide. Effective disease management requires health literacy (HL) interventions to optimize patients' self-management. However, difficulties in communication between patients and healthcare providers often impede improvements in HL. While HL interventions should prioritize enhancing communication quality, current evidence supporting this approach remains limited. Objective: This study aimed to investigate the effectiveness of a Health Literacy Enhancement (HLE) program on CKD knowledge, self-management behaviors, and clinical outcomes in people with CKD. Methods: A quasi-experimental study using a two-group pretest-posttest design was conducted from December 2022 to March 2023. Fifty-two participants with stage 3 to 4 CKD, recruited from outpatient CKD clinics in two district hospitals in Central Thailand, were divided into two groups. Participants in the experimental group (n = 25) received the HLE Program based on Baker's HL concept, while the control group (n = 27) received usual care for 12 weeks. Data were collected twice before and after the 12-week program using a demographic form, CKD knowledge, CKD self-management behaviors (SMBs), and clinical outcomes, including blood pressure (BP), hemoglobin A1c (HbA1c), estimated glomerular rate (eGFR), body mass index (BMI), and waist circumference (WC). Data were analyzed using descriptive statistics, Chi-square, Paired t-test, and Independent t-test. Results: Following the HLE Program, the experimental group had a significantly higher score in CKD knowledge (t = 8.79, p <0.001) and self-management behaviors (SMBs) (t = 7.70, p <0.001). They also achieved a better average estimated glomerular filtration rate (eGFR) (t = 3.14, p<0.01) and had lower systolic blood pressure (SBP) (t = -2.54, p <0.05) and diastolic blood pressure (DBP) (t = -2.05, p <0.05) compared to the control group and their baseline measures. The effect sizes (Cohen's d) were substantial, indicating large effects for CKD knowledge (2.44), self-management behaviors (2.14), and eGFR (0.87), while SBP (-0.71) and DBP (-0.55) indicated medium effects. However, no significant differences were observed in HbA1c, BMI, and WC. Conclusion: The HLE program can enhance effective patient-provider communication using plain language, leading to significant improvements in CKD knowledge and SMBs, as well as clinical outcomes, including eGFR and BP. Nurses should implement this program to enhance HL in people with CKD, leading to effective self-management and helping slow the progression of the disease. Trial Registry Number: Thai Clinical Trials Registry (TCTR20240920001)